High levels of malic acid production by the bioconversion of corn straw hydrolyte using an isolated Rhizopus delemar strain - Li, Xingjiang; Liu, Y.; Yang, Y.; Zhang, H.; Wang, H.; Wu, Y.; Zhang, M.; Sun, T.; Cheng, J.; Wu, X.; Pan, L.; Jiang, S.; et al. (Korean Society for Biotechnology and Bioengineering, 2014)
The microbial fermentation of malic acid, which is one of the most important organic acid platforms used widely in food and chemical engineering, has attracted considerable interest. A malate production strain was isolated, a mutation was induced, and regulation of the metabolic network was then conducted. The identification results showed that the malic acid production strain, HF- 119, belonged to Rhizopus delemar. An analysis of the metabolic pathway showed that the malic acid flux of this strain occurred through three main pathways, and many byproducts, such as succinic acid, fumaric acid and ethanol, were produced. Although corn straw hydrolyte was used, the metabolism of xylose was not as rapid as that of glucose. Subsequently, breeding of the strains and regulation of the metabolic network resulted in an increase in malate yield, and the strain HF-121 produced more than 120 g/L malic acid within 60 h. The ability to produce malic acid from biomass hydrolyte highlights the industrial development potential of this strain.